Anatomical diversity of brachial plexus with embryological and clinical perspectives: a review - Farhat, Rizwana (International Journal of Research in Medical Sciences, 2025)
The brachial plexus (BP) is the main neural source for the upper limb, and its anatomical variations are highly significant in clinical practice. ​ It is a complex network of nerves that plays a crucial role in providing motor and sensory innervation to the upper limb. ​ The clinical importance of the brachial plexus makes it essential for clinicians, surgeons, radiologists, and anaesthesiologists. ​Anatomical variations in its structure and connections with neighbouring nerves can complicate surgical procedures, diagnostic evaluations, and the management of nerve disorders. ​ Variations in the upper limb nerves, such as the absence of certain nerves, interconnections, or unusual pathways, are common anatomical occurrences that can greatly affect clinical diagnosis and treatment. ​ These variations may change innervation patterns or contribute to nerve compression syndromes, resulting in atypical clinical presentations. ​ This review highlights the prevalence of upper limb variations and their clinical significance, stressing the importance of anatomical knowledge for accurate diagnosis and treatment. ​ It also discusses the findings from recent studies and underscores the need for ongoing research to enhance diagnostic precision and surgical outcomes.